What drives buycotters, boycotters and dualcotters? An analysis of political consumerism in Spain - Novo Vázquez, Amparo; Vicente, María Rosalía (Empiria. Revista de metodología de ciencias sociales, 2024)
Political consumerism, as a means of participation through the marketplace, is increasing in most Western democracies. Consequently, companies have been obliged to make themselves accountable to customers. This paper analyses the factors associated with three types of political consumers: boycotters, buycotters, and dualcotters as opposed to those consumers who are not politically involved. Using data from a representative sample of the Spanish population, we focus on the role that the self-perceived efficacy of individuals as consumers plays on political consumerism. Results show that the predictors of the behaviour of boycotters and buycotters are generally different. Internal political efficacy is significant for dualcotters and buycotters whereas consumer efficacy is more predictive in the case of boycotters. The use of social networks is common to all political consumers. El consumo político, como medio de participación a través del mercado, está aumentando en la mayoría de las democracias occidentales. En consecuencia, las empresas se han visto obligadas a rendir cuentas ante los clientes. Este artículo analiza los factores asociados a tres tipos de consumidores políticos: los que boicotean, los que compran y los realizan ambas acciones en oposición a aquellos consumidores que no están implicados políticamente. Utilizando datos de una muestra representativa de la población española, nos centramos en el papel que la eficacia interna de los individuos juega en el consumo político. Los resultados muestran que los predictores del comportamiento de los boicoteadores y los compradores son, en general, diferentes. La eficacia política interna es significativa para los que realizan ambas acciones y los que compran, mientras que la eficacia del consumidor es más predictiva en el caso de los que realizan boicot. El uso de las redes sociales es común a todos los consumidores políticos. Financiación This work was funded by the Spanish Ministry of Economy and Competition, the Spanish State Research Agency and one European Regional Development Fund projects: “Political Food Consumption: Citizens, Activists and Institutions (CSO2016- 76293R)”.